1991
DOI: 10.1128/jvi.65.11.5663-5672.1991
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of a type D retrovirus from B-cell lymphomas of a patient with AIDS

Abstract: An atypical syncytial variant of a high-grade Burkitt's-type B-cell lymphoma from a patient with AIDS who was seropositive for human immunodeficiency virus type 1 was studied. A productive type D retrovirus infection was identified in early-passage cell lines derived from two lymphomas from this patient. Nucleotide and amino acid sequence analysis as well as immunologic reactivity indicated that the isolated virus was highly related to Mason-Pfizer monkey virus (MPMV). MPMV is an immunosuppressive type D retro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…The most convincing evidence for human SRV infection is presented in a case report describing the isolation of virus and SRV transcripts in lymphoma tissue from an HIV/AIDS patient. This individual was additionally seropositive for antibodies directed against multiple viral proteins although they had no known nonhuman primate exposure (Bohannon et al, 1991). Serological and molecular techniques were also used to demonstrate possible SRV exposure with a relatively high frequency in healthy individuals from Guinea (Morozov et al, 1996).…”
Section: Zoonotic Potentialmentioning
confidence: 99%
“…The most convincing evidence for human SRV infection is presented in a case report describing the isolation of virus and SRV transcripts in lymphoma tissue from an HIV/AIDS patient. This individual was additionally seropositive for antibodies directed against multiple viral proteins although they had no known nonhuman primate exposure (Bohannon et al, 1991). Serological and molecular techniques were also used to demonstrate possible SRV exposure with a relatively high frequency in healthy individuals from Guinea (Morozov et al, 1996).…”
Section: Zoonotic Potentialmentioning
confidence: 99%
“…An interesting report by Aziz et al (1989) indicated that a defective mouse leukaemia virus had the ability to cause a severe immunodeficiency disease, indicating strong parallel with the lentiviruses. Viruses of the genus oncovirus D do not induce tumours, but syncytia are detected in vitro (Bohannon et al, 1991) and in vivo together with a persistent non-lytic infection. The spherical immature core of type D oncoviruses, which possesses a marked subunit structure, initially forms in the cytoplasm and buds through the plasma membrane ( Fig.…”
Section: Retrovirusesmentioning
confidence: 99%
“…However, when the virus was inoculated into the juvenile rhesus monkeys, it did result in an immunosuppressive disease, including lymphadenopathy, thymic atrophy, weight loss, and death to facultative organisms, similar to the disease process seen with simian acquired immunodeficiency syndrome (AIDS) [21,22]. It was later discovered that the M-PMV is related to, but distinct from, the type D retroviruses that are responsible for simian AIDS [6,7,14,16,20,23,24,29,36].…”
Section: Discussionmentioning
confidence: 99%
“…And because less than 10% of breast cancers can be linked to a family history, a virus seems a likely possibility [43]. While a human breast cancer virus has never been isolated [45], there have been several reports of viral particles similar in morphology to M-PMV in cell lines derived from human tumors [7,11,25,42,45,53,55]. Although M-PMV readily infects human cells, the disease-causing potential in humans is still unknown [45].…”
Section: Discussionmentioning
confidence: 99%